Systemic benefit of radiation therapy via abscopal effect - Craig, Daniel J.; Ambrose, Stephanie; Stanbery, Laura; Walter, Adam; Nemunaitis, John (Frontiers in Oncology, 2022)
Evidence of systemic activity related to localized RT in cancer management is rare. However, enhancement in immune response via immunotherapy followed by localized RT has shown evidence of tumor shrinkage to non-irradiated metastatic disease thereby inducing “abscopal effect.” Combined induction of cGAS-STING pathway and activation of IFN-gamma signaling cascade related to RT within an activated immune environment promotes neoantigen presentation and expansion of cytotoxic effector cells enabling enhancement of systemic immune response. Proposed mechanism, case examples and clinical trial evidence of “abscopal effect” benefit are reviewed. Results support strategic therapeutic testing to enhance “abscopal effect.”